CLASSIFICATION OF FAILURES AND DAMAGES OF STEEL SILOS (Academic journal Industrial Machine Building Civil Engineering, 2017)
Causes of silo damages and collapse were analyze; foundations of their correctly maintenance were examined. Keywords: steel silo, damages, collapse.